The real-time dynamic holographic display of LN:Bi,Mg crystals and defect-related electron mobility - Shuolin Wang; Yidong Shan; Dahuai Zheng; Shiguo Liu; Fang Bo; Hongde Liu; Yongfa Kong; Jingjun Xu (Opto-Electronic Advances, 2022)
Holographic display has attracted widespread interest because of its ability to show the complete information of the object and bring people an unprecedented sense of presence. The absence of ideal recording materials has hampered the realization of their commercial applications. Here we report that the response time of a bismuth and magnesium co-doped lithium niobate (LN:Bi,Mg) crystal is shortened to 7.2 ms and a sensitivity as high as 646 cm/J. The crystal was used to demonstrate a real-time holographic display with a refresh rate of 60 Hz, as that of the popular high-definition television. Moreover, the first-principles calculations indicate that the electron mobility while Bi occupying Nb-site is significantly greater than that in Li-site, which directly induces the fast response of LN:Bi,Mg crystals when the concentration of Mg is above its doping threshold.